One Year Incidence of Atrial Septal Defect after PV Isolation: A Comparison Between Conventional Radiofrequency and Cryoballoon Ablation. Issue 9 (12th June 2015) - MUGNAI, GIACOMO; SIEIRA, JUAN; CICONTE, GIUSEPPE; HERVAS, MARTA SORIANO; IRFAN, GHAZALA; SAITOH, YUKIO; HÜNÜK, BURAK; Ströker, ERWIN; VELAGIC, VEDRAN; WAUTERS, KRISTEL; TONDO, CLAUDIO; MOLON, GIULIO; et al.
<x xml:space="preserve">Abstract</x> Background Transseptal (TS) catheterization is needed to access the left heart during pulmonary vein isolation (PVI) procedures. In the radiofrequency (RF) ablation procedure, left atrial access is commonly achieved with a double TS puncture; cryoballoon (CB) ablation usually requires only a single TS puncture. Our aim was to compare the incidence of iatrogenic septal defect (IASD) between double transseptal conventional RF and CB ablation. Methods and Results Individuals having undergone PVI as index procedure by RF or CB ablation and a subsequent transesophageal echocardiography examination during postablation follow‐up in our center were consecutively included. A total of 127 patients formed the study group (92 males; mean age 60 ± 11 years). IASD was present in 17 patients (13.4%) after a mean follow‐up time of 11.6 months. The incidence of IASD at 1‐year follow‐up following PVI was significantly higher in the CB ablation group compared with the RF ablation group (22.2% vs 8.5%; P = 0.03). Mean IASD diameter was larger in the CB group (0.60 cm × 0.50 cm vs 0.44 cm × 0.35 cm) without statistical significance. Only left to right atrial shunt was observed. No adverse events were recorded in these patients during the follow‐up. Conclusions the incidence of IASD at 1‐year follow‐up following CB ablation procedure for PVI is significantly higher with respect to RF procedures. Although no adverse clinical events were recorded in patients with persistence of IASD, more detailed echocardiographic examinations might be advised in all individuals exhibiting this finding.